Using LMS Log Data to Explore Student Engagement with Coursework Videos - Suzanne Maloney; Megan Axelsen; Linda Galligan; Joanna Turner; Petrea Redmond; Alice Brown; Marita Basson; Jill Lawrence (Online Learning, 2022)
Driven by the increased availability of Learning Management System data, this study explored its value and sought understanding of student behaviour through the information contained in activity level log data. Specifically, this study examined analytics data to understand students’ engagement with online videos. Learning analytics data from the MoodleTM and Vimeo® platforms were compared. The research also examined the impact of video length on engagement, and how engagement with videos changed over the course of a semester when multiple video resources were used in a course. The comparison in platform learning analytics showed differences in metrics thus offering a caution to users relying on unidimensional metrics. While the results support the notion that log data do provide educators with an opportunity for review, the time and expertise in extracting, handling, and using the data may stifle its widespread adoption.